Ethanolamine activates a sensor histidine kinase regulating its utilization in Enterococcus faecalis - Del Papa, María Florencia (2008)
Enterococcus faecalis is a gram-positive commensal bacterium of the human intestinal tract. Its opportunistic pathogenicity has been enhanced by the acquisition of multiple antibiotic resistances, making the treatment of enterococcal infections an increasingly difficult problem. The extraordinary capacity of this organism to colonize and survive in a wide variety of ecological niches is attributable, at least in part, to signal transduction pathways mediated by two-component systems (TCS). Here, the ability of E. faecalis to utilize ethanolamine as the sole carbon source is shown to be dependent upon the RR-HK17 (EF1633-EF1632) TCS. Ethanolamine is an abundant compound in the human intestine, and thus, the ability of bacteria to utilize it as a source of carbon and nitrogen may provide an advantage for survival and colonization. Growth of E. faecalis in a synthetic medium with ethanolamine was abolished in the response regulator RR17 mutant strain. Transcription of the response regulator gene was induced by the presence of ethanolamine. Ethanolamine induced a 15-fold increase in the rate of autophosphorylation in vitro of the HK17 sensor histidine kinase, indicating that this is the ligand recognized by the sensor domain of the kinase. These results assign a role to the RR-HK17 TCS as coordinator of the enterococcal response to specific nutritional conditions existing at the site of bacterial invasion, the intestinal tract of an animal host.